Answer:
Not a true statement.
Step-by-step explanation:
8(6-4)=12
8(2)=16, not 12.
Anyway
so the recursive rule tells the relationship between the previous term and the term we want to find
given
an=2n+11
it is clear that the first term is 13
2nd term is 15
3rd term is 17
each term increases by 2
so
a term is equal to the previous term plus 2
an=a(n-1)+2
the first one is the answer
Let's simplify step-by-step.
3y-6+7y-4y
=3y+ -6+7y+ -4
Combine Like Terms.
=3y+ -6 +7y+ -4y
=6y+ -6
Answer:
6y-6
Answer:
Average rate of change of function is -2.
Step-by-step explanation:
Given
.
we have to find the average rate of change for the quadratic function from x=−2 to x = 2.
![f(-2)=\frac{-1}{4}(-2+4)^2-8=\frac{-1}{4}(4)-8=-9](https://tex.z-dn.net/?f=f%28-2%29%3D%5Cfrac%7B-1%7D%7B4%7D%28-2%2B4%29%5E2-8%3D%5Cfrac%7B-1%7D%7B4%7D%284%29-8%3D-9)
The average rate of change of the function f(x) on interval [-2,2] is
![\frac{f(b)-f(a)}{b-a}=\frac{f(2)-f(-2)}{2-(-2)}=\frac{-17-(-9)}{4}=\frac{-8}{4}=-2](https://tex.z-dn.net/?f=%5Cfrac%7Bf%28b%29-f%28a%29%7D%7Bb-a%7D%3D%5Cfrac%7Bf%282%29-f%28-2%29%7D%7B2-%28-2%29%7D%3D%5Cfrac%7B-17-%28-9%29%7D%7B4%7D%3D%5Cfrac%7B-8%7D%7B4%7D%3D-2)